Letter from Louis Pasteur to Dr. Becar, 1884, and letter from Pasteur to an unidentified director, 1882 - Pasteur, Louis (1882)
In the first letter Louis Pasteur turns down Dr. Becar's offer to allow Pasteur to perform experiments on him rather then on animals. In the second letter Pasteur endeavors to find work for a young assistant named Antonio Domingo.
Keywords: Microbiologists; Chemists; Pasteur, Louis, 1822-1895